PEMBERDAYAAN UMKM MELALUI PELATIHAN KOMBUCHA UNTUK MENINGKATKAN KREATIVITAS DAN NILAI TAMBAH PRODUK - Ziana Warsani; Affan Gaffar; Soufa Malita (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, yet they still face limitations in product innovation and value-added development, particularly in the functional food sector. This community service program aims to enhance the knowledge, skills, and creativity of MSMEs through training in the production of probiotic kombucha tea. The program was conducted in June 2024, involving 25 MSMEs assisted by the East Lombok Regency Cooperatives and MSMEs Office. The implementation method used a participatory approach, encompassing needs analysis, conceptual outreach and education, hands-on training in kombucha production, packaging-based product innovation, and activity evaluation. The results showed that participants were able to follow the stages of kombucha production, understand the importance of sanitation, and begin to develop creativity through packaging design. This activity demonstrates the effectiveness of practice-based training in increasing MSME capacity and encouraging the development of innovative and value-added functional food-based businesses.